Economic Policy Making and Business Culture : Why Is Russia So Different? - Dyker, David A. (Imperial College Press, 2011)
The book addresses the fundamental problems in Russian society, and in Russia's relations with the rest of the world. Why do Russians tend to react differently from 'us' in given diplomatic or business situations? Why do they find the notion of a contract difficult to grasp? Why do they seem hostile to the principle of the level playing field? How do they see Russia's position within the globalised economy? In order to probe these issues, the author begins with a historical analysis, looking at the pattern of political and economic development since Tsarist times, always asking the questions.